THE CHARACTERISTICS OF PSEUDO-RELIGION: A Case Study of the Documentary Film In the Name of God - A Holy Betrayal - Bonnarty Steven Silalahi (Sekolah Tinggi Teologi Widya Agape dan Perkumpulan Teolog Agama Kristen Indonesia, 2023)
The documentary film